TANDA-TANDA VERBAL DAN VISUAL DARI PESERTA INTERAKTIF DALAM POSTER FILM SPIDER-MAN - Shella Puspita Dewi (Universitas 17 Agustus 1945 Surabaya, 2022)
Advertisements contain a variety of visual and verbal signs that have their own meaning. The study aims to investigate more about Multimodal Discourse Analysis related to Spider-Man movie posters. To this end, researchers conducted a review of the relation of visual and verbal signs with interactive participants (audiences) with nine (9) posters from the superhero movie